PERUBAHAN KADAR IODIUM URIN, TSH, DAN T4 BEBAS PADA WUS SETELAH PEMBERIAN GARAM DOSIS 30-35 ppm KIO3 - Yusi Dwi Nurcahyani; Nur Ihsan; Suryati Kumorowulan (Media Gizi Mikro Indonesia, 2017)
Background. In several countries, iodine deficiency has been turned into iodineexcess. These iodine excess due to poor monitoring of iodine concentration onsalt, which cause high and uneven iodine rations. The objective of the study wasto determine if intervention of 30-35 ppm iodized salt improves UIE, TSH and fT4level in childbearing age women. Methods. This is a quasi-experimental study byproviding 30-35 ppm KIO3 iodized salt for 6 months on childbearing age women inIDD mild endemic area (n=71). The control group were only measured by iodine saltconsumption of each monthly used (n=76). The study conducted in in Bener villagePurworejo. Urinary iodine concentration (UIC), TSH and fT4 were measured atbaseline and endline. TSH and fT4 level were measured using ELISA method. UIEwas analysed using APDM method. Result. Subject characterisitcs of each groupare not much different. Iodine concentration median (range) of treatment group andcontrol group were 149 (20-400) μg/ L and 160 (28 – 698) μg/ L, respectively. MeanTSH level which were normal before intervention (3.03 ± 1.19 μIU/ ml vs 2.52 ±1.29 μIU/ ml), improved significantly after intervention compared to the control group(2.03 ± 1.28 μIU/ ml vs 2.71 ± 1.66 μIU/ ml). Mean free T4 level which were normalbefore intervention (1.29 ± 0.29 ng/ dl vs 1.32 ± 0.24 ng/ dl), decreased significantlyafter intervention compared to the control group (1.04 ± 0.24 ng/ dl vs 1.18 ± 0.43ng/ dl). Conclusion. 30 – 35 ppm iodized salt Intervention for 6 months was able toprovide iodine requirement, improve level of TSH and maintain level of fT4 in normallevel. Keywords: iodine urine concentration, iodized salt intervention, thyroid function,women of childbearing age